Nursing diagnoses associated with the national policy for health promotion - Camila Maciel Diniz (Universidad de Antioquia, 2017)
Objective. To identify the relationships between nursing diagnoses proposed by NANDA-I taxonomy II and the priority themes (PT) of the National Policy for Health Promotion (PNPS in Portuguse).